2020
DOI: 10.3390/s20051283
|View full text |Cite
|
Sign up to set email alerts
|

Automatic, Qualitative Scoring of the Interlocking Pentagon Drawing Test (PDT) Based on U-Net and Mobile Sensor Data

Abstract: We implemented a mobile phone application of the pentagon drawing test (PDT), called mPDT, with a novel, automatic, and qualitative scoring method for the application based on U-Net (a convolutional network for biomedical image segmentation) coupled with mobile sensor data obtained with the mPDT. For the scoring protocol, the U-Net was trained with 199 PDT hand-drawn images of 512 × 512 resolution obtained via the mPDT in order to generate a trained model, Deep5, for segmenting a drawn right or left pentagon. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 43 publications
0
14
0
Order By: Relevance
“…In this study, we were able to fine-tune a pre-trained CNN for PCT scoring without any special adjustments just by preparing the teacher data. Contrarily, in the study that evaluated PCTs using object or feature detection, it was necessary to set up a system to detect the features of PCTs that would be scored as correct answers 5 , 6 . The usefulness of fine-tuned CNN to evaluate the clock drawing test and the Rey-Osterrieth complex figure copying test has also been reported 16 , 17 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this study, we were able to fine-tune a pre-trained CNN for PCT scoring without any special adjustments just by preparing the teacher data. Contrarily, in the study that evaluated PCTs using object or feature detection, it was necessary to set up a system to detect the features of PCTs that would be scored as correct answers 5 , 6 . The usefulness of fine-tuned CNN to evaluate the clock drawing test and the Rey-Osterrieth complex figure copying test has also been reported 16 , 17 .…”
Section: Discussionmentioning
confidence: 99%
“…Computerized scoring of figure copying tests can be considered reliable because the rater experience does not affect the scoring. A recent study reported the robustness of automated quantitative scoring of PCT has been based on information, such as the number or coordinates of pentagons, obtained from object (or feature) detection 5 , 6 . However, since patients with dementia often redraw figures many times, or sometimes copy in close proximity to a model figure 7 , there is a possibility that detection may not be successful due to many artifacts.…”
Section: Introductionmentioning
confidence: 99%
“…To the aim, visual parameter features such as number of angles, distance/intersection, closure/opening, rotation and closing-in where considered with an Artificial Neural Network classifier [6]. Park et al [75] have recently adopted a mobile device to acquire timestamps, x-y coordinates and touchevents. In this case, raw data were processed by means of U-Net (a convolutional network) to automatically segment angles, distance/intersection between the two drawn figures, closure/opening of the drawn figure contours.…”
Section: Pentagon Testmentioning
confidence: 99%
“…Motor testing and speech data can distinguish PD cases from controls [223]. Park et al [224] developed a mobile application to automatically evaluate the interlocking pentagon drawing test using a U-Net architecture.…”
Section: Smartphone / Sensor Datamentioning
confidence: 99%